Charge Radii of Neutron Deficient Fe 52,53 Produced by Projectile Fragmentation - Minamisono, K.; Rossi, D. M.; Beerwerth, R.; Fritzsche, S.; Garand, D.; Klose, A.; Liu, Y.; Maaß, B.; Mantica, P. F.; Miller, A. J.; Müller, P.; Nazarewicz, W.; et al. (Physical Review Letters, 2016)
Bunched-beam collinear laser spectroscopy is performed on neutron deficient Fe52,53 prepared through in-flight separation followed by a gas stopping. This novel scheme is a major step to reach nuclides far from the stability line in laser spectroscopy. Differential mean-square charge radii δr2© of Fe52,53 are determined relative to stable Fe56 as δr2 ©56,52=-0.034(13) fm2 and δr2 ©56,53=-0.218(13) fm2, respectively, from the isotope shift of atomic hyperfine structures. The multiconfiguration Dirac-Fock method is used to calculate atomic factors to deduce δr2 ©. The values of δr2 © exhibit a minimum at the N=28 neutron shell closure. The nuclear density functional theory with Fayans and Skyrme energy density functionals is used to interpret the data. The trend of δr2 © along the Fe isotopic chain results from an interplay between single-particle shell structure, pairing, and polarization effects and provides important data for understanding the intricate trend in the δr2 © of closed-shell Ca isotopes.
CRIS-Team Scopus Importer:2023-07-24